2014
DOI: 10.1371/journal.pone.0113014
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Diversity of Bacterioplankton Communities in Surface Water of Northern South China Sea

Abstract: The South China Sea is one of the largest marginal seas, with relatively frequent passage of eddies and featuring distinct spatial variation in the western tropical Pacific Ocean. Here, we report a phylogenetic study of bacterial community structures in surface seawater of the northern South China Sea (nSCS). Samples collected from 31 sites across large environmental gradients were used to construct clone libraries and yielded 2,443 sequences grouped into 170 OTUs. Phylogenetic analysis revealed 23 bacterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Finally, in the Bacteroidetes, Cytophagales OTU826306 (correlation coefficient with CH 4 = 0.33, p = 0.05), was most similar to microorganisms from a variety of marine environments including surface seawater (Li et al, 2014), seawater particles (D'Ambrosio et al, 2014) and corals (Sunagawa et al, 2010). As discussed above, the Cytophagales species described here is not closely related to a known hydrocarbon degrader, thus why its abundance is significantly correlated with CH 4 concentrations is unknown.…”
Section: Euphotic Zone Bacterioplankton Structure and Diversitymentioning
confidence: 71%
“…Finally, in the Bacteroidetes, Cytophagales OTU826306 (correlation coefficient with CH 4 = 0.33, p = 0.05), was most similar to microorganisms from a variety of marine environments including surface seawater (Li et al, 2014), seawater particles (D'Ambrosio et al, 2014) and corals (Sunagawa et al, 2010). As discussed above, the Cytophagales species described here is not closely related to a known hydrocarbon degrader, thus why its abundance is significantly correlated with CH 4 concentrations is unknown.…”
Section: Euphotic Zone Bacterioplankton Structure and Diversitymentioning
confidence: 71%
“…Gong et al (2015) have identified that water depth was the debisive fabtor to shape biogeography pattern of benthib mibrobial eukaryotes in the surfabe sediments of boastal sea. Our previous study (Li et al 2014) also displayed that water depth played a surprisingly signifibant role in shaping babterial biogeography in the upper 5 meters of water bolumn bharabterized with bomplex birbulation systems. We bonsider that water depth may funbtion as a bomprehensive proxy of multiple physibobhemibal parameters rather than direbtly affebt mibrobial diversity.…”
Section: Introdubtionmentioning
confidence: 73%
“…In addition, the distribution of the most abundant picophytoplankton groups, such as Prochlorococcus and Synechococcus, was found to be significantly influenced by warm or cold eddies (Jing & Liu, 2012;Wang, Tan et al, 2016). Bacterial communities have also been found to be influenced by cyclonic (Zhang, Jiao, Sun, Hu, & Zheng, 2011;Zhang, Zhao, Sun, & Jiao, 2011) and anticyclonic (Li et al, 2014) eddy perturbations.…”
mentioning
confidence: 94%
“…In addition, the distribution of the most abundant picophytoplankton groups, such as Prochlorococcus and Synechococcus , was found to be significantly influenced by warm or cold eddies (Jing & Liu, ; Wang, Tan et al., ). Bacterial communities have also been found to be influenced by cyclonic (Zhang, Jiao, Sun, Hu, & Zheng, ; Zhang, Zhao, Sun, & Jiao, ) and anticyclonic (Li et al., ) eddy perturbations. For example, the distributions of some deep‐water groups were found to exhibit isopycnal uplift (Zhang, Jiao et al., ), and diazotrophic Proteobacteria were found to attain new nitrogen from mesoscale cyclonic eddies, which contributed to nitrogen fixation (Zhang, Zhao et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation